RISK FACTORS FOR STUNTING AMONG ELEMENTARY SCHOOL STUDENTS - Sunarti, Sunarti; Wiarisa, Hesty; Wahyuningsih, Nur Endah; Setiani, Onny (Krafon Publishing, 2019)
Introduction: Stunting is a situation where the child's height measured by the height by age TB/U is below minus two standard deviations ( -2SD) on nutritional status table WHO child growth standards. The prevalence of stunting in children of school age (5-12 years) in Indonesia reached 30.7% prevalence in Magelang reached 30%.The results of monitoring of nutritional status of children in 2015 in the District Ngablak show as much as 32.7% of children are stunted. Analysis of risk factors for stunting in children of primary school age in the District of Magelang Ngablak. Methods: The study was observational research with. cross sectional approach. Subject were students of public primary schools of the Ngablak District ware taken as 72 samples. Collecting data by questionnaires, examination of urine iodine. Results: The results of Chi square test showed risk factors for stunting among at elementary school students of Ngablak District Magelang Regency is nutritional status (p=0.007), history of exposure to pesticides (p=0.006), and iodine urine (EIU) with (p=0.033). Conclusion: The results of logistic regression analysis showed nutritional status (p=0.017 expB=3.945), history of exposure to pesticides (p=0.020 expB=3.725) significantly the incidence of stunting in children of primary school age Ngablak in the District of Magelang.